The Effect of Digital Transformation, User Experience, and User Interface on Customer Loyalty in Technology Startups in Bandung - Frans Sudirjo; Dewi Endah Fajariana; Arnes Yuli Vandika; Unggul Sagena (Westscience Press, 2024)
This study investigates the influence of digital transformation, user experience (UX), and user interface (UI) on customer loyalty in technology startups in Bandung, Indonesia. A quantitative approach was employed, with data collected from 150 respondents using a Likert scale ranging from 1 to 5. The data were analyzed using SPSS version 26, and multiple regression analysis was used to determine the significance of the relationships between the variables. The results reveal that digital transformation, UX, and UI all have positive and significant effects on customer loyalty, with UX being the strongest predictor. These findings provide important insights for technology startups in Bandung, suggesting that enhancing digital processes, optimizing UX, and refining UI design can foster greater customer loyalty. This study contributes to the growing body of literature on the role of digital transformation and customer-centric design in building long-term customer relationships in the startup ecosystem.